Comparison of Treatment Characteristics of Chronic Suppurative Otitis Media - Pambagyo, Septyan Wahyu; Pratama, Ahmad Ardhani; Rismayanti, Rismayanti; Sulaiman, Andi Baso; Arifuddin, Andi Tenri Sanna (Journal La Medihealtico, 2024)
To improve safe and quality health services, the Central Government has established the 2018 National Guidelines for Medical Services (PNPK) concerning the Management of Chronic Suppurative Otitis Media (CSOM), making it a reference, especially for Primary Health Care. To analyze the treatment characteristics of Chronic Suppurative Media Otitis (CSOM) in Mamajang Primary Health Care, Jongaya Primary Health Care, and Minasa Upa Primary Health Care, Makassar for January 2023-December 2023. This type of research is quantitative with a descriptive method through the cross-sectional study approach. The sampling technique used is total sampling. The data collection technique uses secondary data in the form of medical records of chronic suppurative media otitis (CSOM) patients at the Mamajang Primary Health Care, Jongaya Primary Health Care, and Minasa Upa Primary Health Care, Makassar for the 2023 visit year. Based on research conducted at the in Mamajang Primary Health Care, Jongaya Primary Health Care, and Minasa Upa Primary Health Care, Makassar City 72 people with Chronic Suppurative Media Otitis (CSOM) were found. There are differences in the treatment characteristics of the three Primary Health Care, namely the treatment at the Mamajang Primary Health Care is the most given combination of systemic antibiotics + systemic corticosteroids (46%). In contrast, in the Jongaya Primary Health Care, the most systemic antibiotic treatment (44%) was given. The Minasa Upa Primary Health Care has the most systemic antibiotic treatment (27%) and the combination of systemic antibiotics + systemic corticosteroids (27%) is given the most.